Tax competition among U.S. states: Racing to the bottom or riding on a seesaw? - Robert S. Chirinko; Daniel J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2011)
Dramatic declines in capital tax rates among U.S. states and European countries have been linked by many commentators to tax competition and an inevitable race to the bottom. This paper provides an empirical analysis of the reaction of capital tax policy in a given U.S. state to changes in capital tax policy by other states. The analysis is undertaken with a novel panel dataset covering the 48 contiguous U.S. states for the period 1965 to 2006 and is guided by the theory of strategic tax competition. The latter suggests that capital tax policy is a function of foreign (out-of-state) tax policy, home state and foreign state economic and demographic conditions and, perhaps most importantly, preferences for government services. We estimate this reaction function for the two primary business tax policies employed by states: the investment tax credit rate and the corporate income tax rate. The slope of the reaction function - the equilibrium response of home state to foreign state tax policy - is negative, contrary to many prior empirical studies of fiscal reaction functions. This seemingly paradoxical result is due to two critical elements - controlling for aggregate shocks and allowing for delayed responses to foreign tax changes. Omitting either of these elements leads to a misspecified model and a positively sloped reaction function. Our results suggest that the secular decline in capital tax rates, at least among U.S. states, reflects synchronous responses among states to common shocks rather than competitive responses to foreign state tax policy. While striking given prior findings in the literature, these results are not surprising. The negative sign is fully consistent with qualitative and quantitative implications of the theoretical model developed in this paper. Rather than racing to the bottom, our findings suggest that states are riding on a seesaw.
Keywords: H71; H77; H25; 330; tax competition; state taxation; reaction functions; capital taxation; Steuerwettbewerb; Teilstaat; Reaktionsfunktion; Kapitalertragsteuer; Körperschaftsteuer; Steuerbegünstigung; USA